Identification of multiple independent susceptibility loci in the HLA region in Behcet's disease - DİRESKENELİ, RAFİ HANER (NATURE PUBLISHING GROUP, 2013)
Behcet's disease is an inflammatory disease characterized by recurrent oral and genital ulcers and significant organ involvement. Localizing the genetic association between HLA-B*51 and Behcet's disease and exploring additional susceptibility loci in the human leukocyte antigen (HLA) region are complicated by the strong linkage disequilibrium in this region. We genotyped 8,572 variants in the extended HLA locus and carried out imputation and meta-analysis of 24,834 variants in 2 independent Behcet's disease cohorts from 2 ancestry groups. Genotyped SNPs were used to infer classical HLA alleles in the HLA-A, HLA-B, HLA-C, HLA-DQA1, HLA-DQB1 and HLA-DRB1 loci. Our data suggest that the robust HLA-B*51 association in Behcet's disease is explained by a variant located between the HLA-B and MICA genes (rs116799036: odds ratio (OR) = 3.88, P = 9.42 x 10(-5)). Three additional independent genetic associations within PSORS1C1 (rs12525170: OR = 3.01, P = 3.01 x 10(-26)), upstream of HLA-F-AS1 (rs114854070: OR = 1.95, P = 7.84 x 10(-14)) and with HLA-Cw*1602 (OR = 5.38, P = 6.07 x 10(-18)) were also identified and replicated.
Keywords: MAJOR HISTOCOMPATIBILITY COMPLEX; GENOME-WIDE ASSOCIATION; CLASS-I; GENETIC ASSOCIATION; IL23R-IL12RB2; ALLELES; IL10; MHC